EXTENDED EXPECTRUM BETALACTAMASES IN UROPATHOGEN - NAVIN KUMAR, CHAUDHARY; S MAHADEVA , MURTHY (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Background: Urinary tract is the second most common site of bacterial infections in humans. Gram-negative bacteria (GNB) that possess Extended spectrum Î²-lactamases (ESBLs) genes have proven to be a concern to the medical community because of their high resistance rates to 3rd generation cephalosporins. ESBLs production has been associated with higher morbidity and mortality rates and has been reported inÂ Escherichia coli andÂ Klebsiella pneumoniae. ESBLs are emerging worldwide, making rapid and adequate ESBLs detection crucial for the choice of correct antimicrobial therapy. The aim of the study is to determine the profile of uropathogen, their antibiogram and detection of ESBLs producing strains. Materials and methods: Isolation, identification and antimicrobial susceptibility of organism was done by standard Microbiological procedure. For Gram-negative bacilli ESBLs production was detected by DDST as per CLSI guidelines. Results: Three hundred urine specimens were studied. Significant bacteriuria was present in 35% of specimen. The most common pathogens isolated were Escherichia coli 52.4%. The Resistance pattern of uropathogens was for amikacin (AK) 19.04%, nitrofurantoin (NIT) 40%. We found 55% Gram-negative uropathogen harbored the ESBLs. Majority of ESBLs seen in Klebsiella pneumoniae 60% and Escherichia coli 55%. The ESBLs producing Escherichia coli were highly susceptible to Imipenum 90.90% and Meropenem 94.45%. Conclusions: Escherichia coli are the commonest cause of UTI. Majority of UTI are mono-microbial. Screening of multidrug resistant bacteria especially GNB poses considerable therapeutic challenges in critical care patients because of the production of ESBLs. Amikacin and Nitrofurantoin are the most suitable antibiotics for treatment. Key words: UTI, Uropathogen, Antimicrobial Resistance, ESBL